Oral cancer incidence rates from 1997 to 2016 among men in Taiwan: Association between birth cohort trends and betel nut consumption. (August 2020) - Su, Shih-Yung; Chen, Wei-Ting; Chiang, Chun-Ju; Yang, Ya-Wen; Lee, Wen-Chung
Highlights: Betel nut chewing is possibly the main driver of the cohort effect for oral cancer incidence rates among men in Taiwan. A decrease in smoking prevalence may also have contributed to the reduction in oral cancer incidence after the 1972 birth cohort. An increasing prevalence of alcohol consumption is unlikely to be the reason for the cohort effect. Abstract: Objectives: Oral cancer is the fourth most common cancer among men in Taiwan. Betel nut consumption is a major risk factor for oral cancer, but the association between betel nut chewing and the long-term secular trend of oral cancer incidence is unclear. Materials and methods: We conducted an age-period-cohort analysis to examine the incidence rates of oral cancer among men in Taiwan from 1997 to 2016. Results: The oral cancer incidence rate among men doubled between 1997 and 2009, but the trend leveled off thereafter. Oral cancer incidence rates in the oldest age group (80–84 y) were approximately 85 times those of the youngest group (25–29 y). The period effect was weak, and the cohort effect exhibited a drastically increasing trend from 1917 (midyear for 1913–1921) to 1972 (1968–1976) birth cohorts and then a decreasing trend afterward. The Spearman rank correlation coefficient between the cohort effects on oral cancer incidence among men and the average consumption of betel nut with a lag time of 30 years had a significant and extremely high value of 0.993. Conclusions: Our findings suggest that betel nut chewing is the main driver of the cohort effect for oral cancer incidence rates among men in Taiwan. In addition to reduced betel nut consumption, a decrease in smoking prevalence may also have contributed to the reduction in oral cancer incidence after the 1972 birth cohort; moreover, the increasing prevalence of alcohol consumption in Taiwan is unlikely to be the reason for the cohort effect for oral cancer.